(untitled) (Chichester, West Sussex, U.K.,Hoboken, N.J., 2015)
This book is an invaluable resource for industry-based researchers, academic institutions and professionals working in the area of fungal biology and associated biomolecules for their applications in food technology, microbial and biochemical process, biotechnology, natural products, drug development and agriculture.
Keywords: Lên men nấm,Fungal enzymes; Nghiên cứu,Research